Pemberdayaan Konselor Sebaya di MTs Darussalam Taman dan MTs Muhammadiyah 1 Taman Sidoarjo - Moch. Bahak Udin By Arifin; Eni Fariyatul Fahyuni (Indonesian Journal of Cultural and Community Development, 2018)
Peer counseling is counseling assistance which provided by peers who have been given training to be peer counselors, so that they can provide assistance both individually and groups. Guidance assistance is given to friends who have problems or who has various obstacles in the development of their personality. Peer counselors will provide positive reinforcement because peers have a large influence on individual behavior changes. The purpose of this service is to provide training to students who are given the authority as peer counselors in MTs Darussalam Taman and MTs Muhammadiyah 1 Taman to improving the effectiveness of teacher counseling guidance services. The steps in this service are: First, make observations to each school which is the aim to get an overview of the object, its includes the profile of the school, the number of students, the availability of counseling guidance staff, and information about student problems. Second, collaborating with counseling and classroom teacher teachers, selecting 30 students from grades VII and VIII in each school to become peer counselors. Third, conducting peer counselor training with lecture, question and answer, role play and simulation methods. Fourth, the concelor counseling follows up with mentoring and evaluating, the counseling process carried out by peer counselors. The results of this service are the increasing effectiveness of counseling services through peer counselors in Darussalam Taman MTs and MTs 1 Muhammadiyah Taman.